Growth Hormone and Low Dose Estrogen in Turner Syndrome: Results of a United States Multi-Center Trial to Near-Final Height - Quigley, Charmian A.; Crowe, Brenda J.; Anglin, D. Greg; Chipman, John J. (The journal of clinical endocrinology and metabolism, 2002)
A cardinal clinical feature of Turner syndrome (TS) is linear growth failure resulting in extreme short stature: the median adult height of untreated women with TS is 143 cm, 20 cm (8 in.) below that of the general female population. In the largest multicenter, randomized, long-term, dose-response study conducted in the United States, 232 subjects with TS received either 0.27 or 0.36 mg/kg·wk of recombinant human GH with either low dose ethinyl E2 or oral placebo. The study was placebo-controlled for both GH and estrogen for the first 18 months and remained placebo-controlled for estrogen for its duration. The near-final height of the 99 subjects whose bone age was at least 14 yr was 148.7 ± 6.1 cm after 5.5 ± 1.8 yr of GH started at a mean age of 10.9 ± 2.3 yr; this represents an average increase of 1.3 ± 0.6 sd scores from baseline (TS standard). Height was greater than 152.4 cm (60 in.) in 29% of subjects compared with the expected 5% of untreated patients. Mean near-final heights of subjects who received the lower GH dose, with or without estrogen, were 145.1 ± 5.4 and 149.9 ± 6.0 cm, respectively; those who received the higher GH dose with or without estrogen achieved mean near-final heights of 149.1 ± 6.0 and 150.4 ± 6.0 cm, respectively. Factors that most impacted outcome were younger age, lower bone age/chronological age ratio, lower body weight, and greater height sd score at study entry. This study demonstrates significant GH-induced improvement in height sd score, with correction of height to within the normal channels for a significant number of patients, and provides evidence of a GH dose-response effect. These data also indicate that early administration of estrogen, even at relatively low doses, does not improve gain in near-final height in patients with TS.